THE INFLUENCE OF PRODUCT CHARACTERISTICS AND ADVERTISING EFFECTIVENESS ON BUY INDOSAT PACKAGE CARD - Maininda Prasasti; Daud Arifin; Meylisa Damayanti Br Tarigan; Najwa Syahfitri; Ade Nur Aslamiyah (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
This study is examining influence of knowledge, skill, and adaptation ability of new technology on employee performance of PT Home of Living Arts Indonesia. This analysis includes classical assumption test, multiple regression analysis, hypothesis testing via t test and F, as well as the analysis of the coefficient of determination (R2). Results of analysis using the F test showed that thred of independent variables are knowledge, skill, and social on adaptation ability of new technology have a significant effect on the dependent variable is employee performance of PT Home of Living Arts Indonesia. Results of analysis using the coefficient of determination is known that the variation of performance of 87,6% can be explained by knowledge, skill, and adaptation ability of new technology. While the remaining 12,4% is explained by other variables that are not included in this study.